Analisis Peran Guru Sebagai Fasilitator dalam Literasi Dasar Membaca di Kelas Rendah - Fauziah, Siti Sarah; Lyesmaya, Dyah; Maulana, Luthfi Hamdani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the role of teachers as facilitators in basic reading literacy in lower grades. This research uses descriptive qualitative research. Qualitative emphasizes meaning rather than generalization and the data cannot be resolved with statistical calculations. Qualitative research is research that provides an overview of a phenomenon or situation that occurs. The aim of this research was to determine the role of teachers as facilitators in basic reading literacy in class III at SDN Ranji. The results of the research show that literacy in class III is good and is carried out every day, because there is a teacher's role in providing facilities in the classroom to support literacy activities. The role of the teacher as a facilitator in literacy activities is observed by the author from several indicators, including: Providing facilities for literacy activities , Providing non-physical facilities, acting as a partner, Carrying out duties and functions as a facilitator teacher, literacy environment and reading skills.